2D Model Study of CO2 Plumes in Saline Reservoirs by Borehole Resistivity Tomography. (15th December 2011) - al Hagrey, Said A.
Abstract : The performance of electrical resistivity tomography (ERT) in boreholes is studied numerically regarding changes induced by CO2 sequestration in deep saline reservoirs. The new optimization approach is applied to generate an optimized data set of only 4% of the comprehensive set but of almost similar best possible resolution. Diverse electrode configurations (mainly tripotential α and β ) are investigated with current flows and potential measurements in different directions. An extensive 2.5D modeling (>100, 000 models) is conducted systematically as a function of multiparameters related to hydrogeology, CO2 plume, data acquisition and methodology. ERT techniques generally are capable to resolve storage targets (CO2 plume, saline host reservoir, and impermeable cap rock), however with the common smearing effects and artefacts. Reconstructed tomograms show that the optimized and multiply oriented configurations have a better-spatial resolution than the lateral arrays with splitting of potential and current electrode pairs between boreholes. The later arrays are also more susceptible to telluric noise but have a lower level of measurement errors. The resolution advance of optimized and multiply oriented configurations is confirmed by lower values for ROI (region of index) and residual (relative model difference). The technique acceptably resolves targets with an aspect ratio down to 0.5.